2018
DOI: 10.1038/s41598-018-30632-1
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular events associated with nitrogen deficiency in rice seedling roots

Abstract: Nitrogen (N) deficiency is one of the most common problems in rice. The symptoms of N deficiency are well documented, but the underlying molecular mechanisms are largely unknown in rice. Here, we studied the early molecular events associated with N starvation (−N, 1 h), focusing on amino acid analysis and identification of −N-regulated genes in rice roots. Interestingly, levels of glutamine rapidly decreased within 15 min of −N treatment, indicating that part of the N-deficient signals could be mediated by glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 88 publications
7
52
0
Order By: Relevance
“…However, when KNO 3 or NH 4 Cl was resupplied, it was gradually decreased to basal level within 24 hours while KCl control treatment did not alter OsNLP1 transcript level (Fig. 1I and J), consistent with the previous report that OsNLP1 was induced by N starvation in rice roots (Hsieh et al, 2018). All these data imply that OsNLP1 is N responsive and may play some roles in N utilization or signaling…”
Section: Resultssupporting
confidence: 91%
“…However, when KNO 3 or NH 4 Cl was resupplied, it was gradually decreased to basal level within 24 hours while KCl control treatment did not alter OsNLP1 transcript level (Fig. 1I and J), consistent with the previous report that OsNLP1 was induced by N starvation in rice roots (Hsieh et al, 2018). All these data imply that OsNLP1 is N responsive and may play some roles in N utilization or signaling…”
Section: Resultssupporting
confidence: 91%
“…Nitrogen fertilizer is critical for grain yield and seed quality in many crops, such as wheat, rice, and maize [ 19 , 24 , 25 ]. Moreover, a previous study reported changes of metabolism pathways in rice seedling roots in response to nitrogen deficiency [ 26 ]. However, effects of nitrogen level during seed production on seed vigor are largely unknown in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have found that multiple protein genes are related to nitrogen use efficiency in rice.OsCPK12 participates in the response signal pathway of low nitrogen stress, and overexpression of OsCPK12 enhances rice growth under low nitrogen conditions [59] . Hsieh et al [60] found that the N-regulated genes, Os02g0120100, Os02g0807000 and Os06g0692600 etc., which encode transcription factors, protein kinases and protein phosphatases and may be involved in the regulation of early −N responses in rice roots. The serine/threonine/tyrosine (STY) protein kinase, ACTPK1, enhances ammonium uptake and use, and promotes growth of rice seedlings under sufficient ammonium [61] .…”
Section: Discussionmentioning
confidence: 99%